A Reasearch on Formulation and in Vitro Assessment of a Bilayer NSAID Tablet for Controlled Pain Management - Kacheshwar, Chaudhari Kaweri; Pawar, Priyanka Bajirao; Jadhav, Dr. Vijay B.; Aglawe, Dr. Sachin B.; Aghade, Mr. Karveer B.; Jain, Dr. Nitin P.; Jain, Dr. Usha N. (International Journal of Aquatic Research and Environmental Studies, 2026)
The present investigation was aimed at the formulation and in vitro assessment of a bilayer non-steroidal anti inflammatory drug (NSAID) tablet containing Diclofenac Sodium and Tenoxicam for controlled and effective pain management. Chronic inflammatory and painful conditions often require immediate relief followed by prolonged therapeutic action to maintain adequate drug concentration in the body. Conventional dosage forms generally fail to provide both rapid onset and sustained effect simultaneously, leading to frequent dosing and reduced patient compliance. To overcome these limitations, a bilayer tablet approach was designed in the present study to combine immediate-release and sustained-release drug delivery within a single dosage form. In this formulation, Diclofenac Sodium was incorporated into the immediate-release layer to provide rapid analgesic and anti-inflammatory action, while Tenoxicam was included in the sustained-release layer to maintain prolonged therapeutic activity for extended pain control. The bilayer tablet system was developed using the direct compression method with the help of suitable pharmaceutical excipients such as polymers, binders, diluents, lubricants, and disintegrating agents. The selection of excipients was carried out to achieve optimum tablet integrity, rapid disintegration of the immediate-release layer, and controlled drug release from the sustained-release layer. Prior to compression, the powder blends were evaluated for pre-compression parameters including angle of repose, bulk density, tapped density, Carr’s compressibility index, and Hausner’s ratio to determine their flow characteristics and compressibility behavior. The obtained values indicated acceptable flow properties suitable for tablet manufacturing. The prepared bilayer tablets were further subjected to post-compression evaluation tests such as thickness, hardness, friability, weight variation, disintegration time, and drug content uniformity. All formulations showed satisfactory physicochemical properties and complied with official pharmacopeial specifications. The in vitro dissolution studies were performed using USP dissolution apparatus under suitable dissolution conditions to evaluate the drug release profile of both layers. The immediate-release layer containing Diclofenac Sodium exhibited rapid drug release within a short period, ensuring quick onset of pain relief. In contrast, the Tenoxicam sustained-release layer demonstrated a gradual and controlled drug release pattern over an extended duration, which may help maintain therapeutic plasma concentration for a prolonged period. The optimized formulation showed desirable release kinetics and effective bilayer performance without layer separation or physical instability.